Economic fluctuations and long-term trends in depression: a repeated cross-sectional study in Estonia 2004–2016. Issue 11 (12th August 2019) - Leinsalu, Mall; Reile, Rainer; Stickley, Andrew
Abstract : Background: In the 2000s, the Baltic countries experienced unprecedented credit-driven economic growth that was followed by a deep recession. This study examined the impact of profound macroeconomic changes on population mental health in Estonia in 2004–2016. Methods: Data on 17 794 individuals in the 20– 64 age group were obtained from seven nationally representative cross-sectional surveys. The prevalence of past 30-day depression was calculated for men and women further stratified by sociodemographic characteristics. Multivariable regression analysis was used to assess whether these characteristics were associated with the yearly variation in depression. Results: In 2006, the adjusted prevalence ratio for depression was 0.77 (95% CI 0.64 to 0.93) for men and 0.85 (95% CI 0.74 to 0.97) for women as compared with 2004; in 2010, the prevalence ratio as compared with 2008 for both men and women was 1.22 (95% CIs 1.04 to 1.43 and 1.09 to 1.37, respectively). Among men, the increase in the prevalence of depression in 2008–2010 was statistically significant for 35–64 year olds, ethnic Estonians, those who were married, mid-educated or were employed, whereas among women, a significant increase was observed in 50–64 year olds, Estonians and non-Estonians, those who were not-married, were highly educated or mid-educated, in the mid-income group or were employed. Conclusions: Population mental health is responsive to macroeconomic changes. In less wealthy high-income countries, the greater impact of recession on depression among advantaged groups may relate to a higher debt burden coupled with job insecurity.